Fixed-wing UAV obstacle avoidance algorithm based on real terrain - Mao, Zhiyun; Mo, Li (Journal of physics. Conference series, 2024)
This paper presents an obstacle avoidance algorithm for UAVs based on real terrain constraints. The common obstacle avoidance algorithm often abstracts the obstacle as a sphere or a circle or studies the UAV’s two-dimensional obstacle avoidance on a raster map. With the development of fixed-wing UAVs, UAVs have longer and longer time in the air, longer and longer range, and the low-altitude environment they face is often difficult to simulate with simplified regular shape. Thus, this paper constructs the UAV flight terrain environment using open elevation data and designs an obstacle avoidance algorithm accordingly. When the UAV is tracking the track point, it can better control the UAV to avoid obstacles and fly to the target track point.